2018
DOI: 10.1016/j.shaw.2017.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Determining Sincerity of Effort Based on Grip Strength Test in Three Wrist Positions

Abstract: BackgroundSeveral grip strength tests are commonly used for detecting sincerity of effort. However, there is still no widely accepted standardized sincerity of effort test. Therefore, this study aimed to examine whether grip strength test in three wrist positions could distinguish between maximal and submaximal efforts.MethodsTwenty healthy individuals (10 men and 10 women) with a mean age of 26.7 ± 3.92 years participated in this study. All participants completed two test conditions (maximal and submaximal ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 25 publications
2
24
0
Order By: Relevance
“…25 The individual was seated with their humerus at 0 degrees abduction and neutral rotation, 90 degrees of elbow flexion, and wrist in neutral. 26,27 The average score of the three trials was collected for each hand, and data for the dominant hand was used for analysis. 25…”
Section: Physical Measuresmentioning
confidence: 99%
“…25 The individual was seated with their humerus at 0 degrees abduction and neutral rotation, 90 degrees of elbow flexion, and wrist in neutral. 26,27 The average score of the three trials was collected for each hand, and data for the dominant hand was used for analysis. 25…”
Section: Physical Measuresmentioning
confidence: 99%
“…The findings were in line with a previous study which was conducted in healthy participants. 19 This suggested that the grip strength ratios of N/F and N/E might be used to assess the SOE in people with upper extremity MSDs. The considerable lower grip strength and grip strength ratio found in the SE condition in comparison with ME condition may be explained by a model developed by Kroemer and Marras.…”
Section: Discussionmentioning
confidence: 99%
“…The methodology used in this study was adapted from a previous study. 19 This study was a within‐subject research design comparing between ME and SE during performing grip strength tests in neutral, full flexion, and full extension wrist positions (Figure 1 ). In the ME condition, the participants applied force with 100% effort.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies showed strongest HGS in supinated and weakest HGS in pronated wrist positions [ 28 , 29 ]. Furthermore, reduced HGS was reported when measured in flexed and extended wrist positions, compared with HGS in neutral measurement positions, as well as differences between sitting and standing postures [ 30 , 31 ]. The differences were explained by changes in muscle length in flexed and extended positions, resulting in nonmaximal grip force.…”
Section: Introductionmentioning
confidence: 99%